Methanol adducts leading to the identification of a reactive aldehyde metabolite of CPAQOP in human liver microsomes by ultra‐high‐performance liquid chromatography/mass spectrometry. (28th November 2016) - Martin, Scott; Lenz, Eva M.; Smith, Robin; Temesi, David G.; Orton, Alexandra L.; Clench, Malcolm R.
Abstract : Rationale: The incubation of CPAQOP (1‐[(2 R )‐2‐[[4‐[3‐chloro‐4‐(2‐pyridyloxy)anilino]quinazolin‐5‐yl]oxymethyl]‐1‐piperidyl]‐2‐hydroxy) with human liver microsomes generated several metabolites that highlighted the hydroxyacetamide side chain was a major site of metabolism for the molecule. The metabolites were derived predominantly from oxidative biotransformations; however, two unexpected products were detected by liquid chromatography/ultraviolet/mass spectrometry (LC/UV/MS) and identified as methanol adducts. This observation prompted further LC/MS investigations into their formation. Methods: Three separate incubations of CPAQOP were conducted in human liver microsomes; Naïve, fortified with methoxyamine and fortified with glutathione. Separation was achieved via ultra‐high‐performance liquid chromatography with either methanol or acetonitrile gradients containing formic acid. MS analysis was conducted by electrospray ionisation LTQ Orbitrap mass spectrometry acquiring accurate mass full scan, data‐dependent MS 2 and all ion fragmentation. Results: No methanol adducts were detected by MS when acetonitrile was used in the mobile phase instead of methanol, verifying that a metabolite was reacting with methanol on column. Although this reactive metabolite could not be isolated or structurally characterised by LC/MS directly, product ion spectra of the methanol adducts confirmed addition of methanol on the hydroxyacetamide side chain. Additional experiments using methoxyamine showed the disappearance of the two methanol adducts and appearance of a methoxyamine adduct, confirming the presence of an aldhyde. Product ion spectra of the methoxyamine adduct confirmed addition of methoxyamine to the hydroxyacetamide side chain. Conclusions: The proposed bioactivation of CPAQOP occurred via the reactive aldehyde intermediate, which readily reacted with methanol in the mobile phase to form a pair of isomeric hemiacetal methanol adducts. In acidified methanol the equilibrium favoured the methanol adduct and in acidified acetonitrile it favoured the hydrate; therefore, the reactive aldehyde metabolite was not detected and could not be structurally characterised directly. Copyright © 2016 John Wiley & Sons, Ltd.